Improving early recognition of Creutzfeldt‐Jakob disease mimics in clinical practice. (31st December 2021) - Lazar, Evelyn; Porter, Amanda; Prusinski, Christian C; Dunham, S Richard; Lopez‐Chiriboga, A Sebastian; Day, Gregory S
Abstract: Background: Diagnostic criteria emphasize the use of real‐time quaking‐induced conversion (RT‐QuIC) assays in cerebrospinal fluid (CSF) to identify patients with rapidly progressive dementia (RPD) due to for Creutzfeldt‐Jakob disease (CJD; CDC Diagnostic Criteria; Oct‐2018). Yet, this test is often performed in specialized centers, leading to delays in return of results. There is a need to leverage clinical features and the results of readily available tests to distinguish patients with CJD from those with other causes ('CJD mimics'), including patients with potentially treatment‐responsive RPD. Method: Patients with definite (pathology‐confirmed) or probable CJD (clinical features with positive RT‐QuIC) were identified through retrospective review of Mayo Clinic Enterprise (n=91) and Washington University in St. Louis records (n=14; Jan‐2014 to Dec‐2020). Demographic, clinical details and results of common investigations (e.g., neuroimaging, CSF analyses and electroencephalogram) were compared between CJD cases and 'mimics' who met clinical criteria for probable CJD but did not have CJD. Result: CJD mimics were diagnosed with autoimmune encephalitis (n=8), neurosarcoidosis (n=1), FTLD/MND (n=1) and unknown dementia (n=1), comprising 11/155 (7%) patients enrolled with RPD at study sites. Median [range] ages‐at‐presentation (65.6 [21.9‐81.5] vs 62.4 [32.8‐76.4] years; p=0.09), % females (51% vs 46%; p>0.99) and symptoms/signs were similar between groups, with the exception of motor complaints (e.g., spasms, focal weakness), which were more common in mimics (11/11 vs 55/105; p<0.01). Electroencephalogram findings did not differ between groups. MRI findings compatible with CJD (i.e., restricted diffusion within deep nuclei/cortical ribbon) predominated in cases (80/105 vs 4/11; p<0.01), while elevations in CSF leukocytes (>5 cells/hpf: 6/11 vs 5/103; p<0.01) and protein >45 mg/dL (10/11 vs 43/103; p<0.01) were more common in mimics. Total‐tau levels >1150 pg/mL (76/84 vs 2/10; p<0.01) and 'positive' 14‐3‐3 (67/98 vs 3/10; p=0.03) were frequent in cases. Autoantibodies associated with autoimmune encephalitis were detected in 5/10 mimics but 0/87 cases (p<0.01). Immunosuppressant therapies were provided to 10 mimics and 24 cases, with response limited to mimics. Conclusions: Autoimmune encephalitis, neurosarcoidosis and select neurodegenerative diseases may mimic CJD at presentation. Findings from brain MRI and commonly available CSF tests may facilitate early recognition of mimics, providing an opportunity for early treatment.